An Arthurian Knight in Ivory and Ink: Visualizations of Chrétien de Troyes’ ‘Le Conte du Graal’ in Fourteenth Century Paris - Rush, Katherine Anne (Eikón / Imago, 2021)
Manuscript Bibliothèque nationale de France, MS fr. 12577 and ivory casket Musée du Louvre, OA 122, and are two of three extant fourteenth-century visualizations of Chrétien’s Le Conte du Graal, produced in Paris circa 1310-1330. Although the objects’ shared era of production suggests similarities of iconography, artistic influences, and production methods, little research has been conducted regarding visual and cultural connections between MS fr. 12577 and OA 122. Through iconographic and stylistic analysis of the scenes each artisan depicted within his respective medium, I elucidate how the casket and manuscript’s imagery personifies Perceval’s dual nature, a young knight symbolic of the secular and sacred. As visualizations of Chrétien’s most religiously-minded legend, MS fr. 12577 and OA 122 exemplify the intertwining of the sacred and secular within fourteenth-century French romantic art, specifically within illuminated manuscripts and carved ivory, materials that through their refinement, rarity, and expense, signified leisure, luxury, and nobility. By examining these two opulent objects, I provide insights into their purpose and significance in late medieval France, especially cultural crossover between the porous realms of sacred and secular medieval life.